Batasan Antara Moderasi dan Toleransi Dalam Pendidikan Islam: - Nurnaesih Nurnaesih; Wahyu Hidayat; Wasehudin Wasehudin (Mimbar Kampus: Jurnal Pendidikan dan Agama Islam, 2023)
This research is based on concerns about the phenomena that occur today, becoming an event that strikes our minds. Several incidents cause us to think back and relate these events to the educational process so far.This research will examine moderation and tolerance in Islamic education. So that we can know the limitations that have been stated in the Al-Quran and Al-Hadith. Because Islam has been born with hospitality, Islam is spread in a peaceful way and there is no element of coercion. This research is a literature study that aims to examine moderation and tolerance in the letter Al-Kafirun. Tolerance has existed since the time of the prophet and what is happening now is that violence or radicalism does not come from Islam, but from human understanding in dealing with differences. We live in a country that is large and rich in tribes, religions, customs and languages, so there will be a potential for differences, how can we make those differences a blessing in accordance with the hadith of the prophet, that ikhtilafuummatirahmatun, it is necessary to have values moderation and religious tolerance in carrying out the teachings of the Islamic religion and must be implemented through the world of education. In the context of the ministry of religion, this is related to the implementation of Islamic educational institutions in Indonesia. At various levels, both formal and informal Keywords: Moderation,Tolerance, The Letter Al-Kafirun, Islamic Education